Life-Threatening Hematuria as Initial Presentation of a Complicated Transplant Renal Artery Pseudoaneurysm - Miyara, Santiago J.; Becker, Lance B.; Guevara, Sara; Lau, Lawrence; Nair, Vinay V.; Jandovitz, Nicholas; Fahmy, Ahmed E.; Grodstein, Elliot; Winnick, Aaron M.; Kirsch, Claudia; Rolston, Daniel M.; Bhaskaran, Madhu C.; Hayashida, Kei; Shinozaki, Koichiro; Takegawa, Ryosuke; Cho, Young Min; Cagliani, Joaquin A.; Isa, Arton; Al-Roubaie, Mustafa; Krishnasastry, K. V.; Teperman, Lewis W.; Molmenti, Ernesto P. (International Journal of Angiology, 2020)
In this case report, we describe the clinical course of a complicated transplant renal artery (TRA) pseudoaneurysm, clinically featured by gross and massive hematuria one month after a kidney transplant was performed on a 50 year-old male patient. TRA pseudoaneurysm is a rare but potentially life-threatening complication that may result in bleeding, infection, graft dysfunction/loss, lower limb ischemia/loss, hemorrhagic shock, and death. TRA pseudoaneurysm treatment remains challenging as it needs to be tailored to the patient characteristics including hemodynamic stability, graft function, anatomy, presentation, and pseudoaneurysm features. This publication discusses the clinical scenario of massive gross hematuria that derived from a retroperitoneal hematoma which originated from an actively bleeding TRA pseudoaneurysm. This case highlights the combined approach of endovascular stent placement and subsequent transplant nephrectomy as a last resort in the management of intractable bleeding from a complicated TRA pseudoaneurysm. To the best of our knowledge, this is the first published case report of an actively bleeding TRA anastomotic pseudoaneurysm that caused a massive retroperitoneal bleed that in turn evacuated via the bladder after disrupting the ureter-to-bladder anastomosis. A temporizing hemostatic arterial stent placed percutaneously allowed for a safer and controlled emergency transplant nephrectomy.
Keywords: transplant renal artery pseudoaneurysm; graft-loss; delayed graft function; massive pulmonary embolism; ischemia; cardiac arrest; hemorrhagic shock; sepsis; hematuria